Analisa SWOT Sebagai Dasar Penyusunan Strategi Pembukaan RPL Akademi Kesehatan John Paul II Pekanbaru - Anna Maria (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
This study applied SWOT analysis as a means of justification for Akademi Kesehatan John Paul II Pekanbaru to administer Recognition of Prior Learning program. SWOT analysis internally and externally identified strengths, weaknesses, opportunities, and threat of AKJP II Pekanbaru through interview with 30 respondents. The first interview obtained indicators of strength=15, weakness=7, opportunity=11, threat=10. The second interview obtained a qualitative analysis of each indicator which was subsequently analyzed with IFAS-EFAS matrix with score 1.19 : -0.13 (Quadrant II) outlining AKJP II Pekanbaru had strength along with threat emphasizing to use strengths to exploit long-term opportunities. Concentric diversification strategy was to be applied in which a new program sharing technologies and facilities with current study program may be administered. In conclusion, it supported AKJP II Pekanbaru to administer RPL program for diploma of medical laboratory technology with implementation of IFAS-EFAS evaluation strategies to ensure the administration quality.